Onmyōdō in the Muromachi Period - Yanagihara, Toshiaki (Japanese journal of religious studies, 2013)
This article argues that the significance of the Muromachi period within the history of Onmyōdō has been seriously undervalued and understudied, and demonstrates the importance of the period through a discussion of the careers of the leading onmyōji of the time. It discusses the policies of Ashikaga Yoshimitsu and his promotion of numerous onmyōji to high court ranks, and his performance of various Onmyōdō rituals, such as "the Great Esoteric Rite at Kitayama villa." It then looks at the decline of onmyōji activities after the death of Yoshimitsu and during the administrations of Yoshimochi and Yoshinori. It concludes that the Muromachi period, especially during the reign of Ashikaga Yoshimitsu, was the "golden age" of Onmyōdō, and speculates on why this has been overlooked by scholars.